2010
DOI: 10.1068/i0384
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Everyday Objects on the Basis of Gaborized Outline Versions

Abstract: Using outlines derived from a widely used set of line drawings, we created stimuli geared towards the investigation of contour integration and texture segmentation using shapes of everyday objects. Each stimulus consisted of Gabor elements positioned and oriented curvilinearly along the outline of an object, embedded within a larger Gabor array of homogeneous density. We created six versions of the resulting Gaborized outline stimuli by varying the orientations of elements inside and outside the outline. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 54 publications
5
54
1
Order By: Relevance
“…Deviations in landing position were also smaller for contours with smaller inter-element angles, which are known to be easier to integrate [21,46,47]. This supports an interpretation of the symmetry effect in terms of grouping and not (only) saccade targeting per se.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Deviations in landing position were also smaller for contours with smaller inter-element angles, which are known to be easier to integrate [21,46,47]. This supports an interpretation of the symmetry effect in terms of grouping and not (only) saccade targeting per se.…”
Section: Discussionsupporting
confidence: 70%
“…Compared to natural scenes, contour integration stimuli are inherently cluttered as a result of the placement of many distracter elements to eliminate proximity or density cues, which is a necessary and general limitation of this paradigm that was designed to isolate grouping by good continuation. Although earlier research has shown that participants can reliably identify many everyday object shapes embedded in such Gabor stimuli when presented in central vision [46,47], it is arguably unclear how accurate or detailed participants' perception of contour shape was with our eccentrically presented shapes, and whether participants perceived the complete closed contour.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…These grouping stimuli come in many flavors: textured regions (e.g., Giora & Casco, 2007;Harrison & Feldman, 2009;Julesz, 1981;Lamme, 1995;Nothdurft, 1985;Roelfsema, Lamme, Spekreijse, & Bosch, 2002;Rossi, Desimone, & Ungerleider, 2001;Wolfson & Landy, 1998), oriented line fields (e.g., Li & Gilbert, 2002;Tversky, Geisler, & Perry, 2004), Gabor fields (e.g., Dakin & Baruch, 2009;Demeyer, De Graef, Verfaillie, & Wagemans, 2011;Field, Hayes, & Hess, 1993;Kovács & Julesz, 1993;Machilsen, Pauwels, & Wagemans, 2009;Nygård, Van Looy, & Wagemans, 2009;Persike & Meinhardt, 2008;Sassi, Vancleef, Machilsen, Panis, & Wagemans, 2010;Watt, Ledgeway, & Dakin, 2008), dot lattices (e.g., Bleumers, De Graef, Verfaillie, & Wagemans, 2008;Claessens & Wagemans, 2005Kubovy & Wagemans, 1995;Põder, 2011), Glass patterns (e.g., Khuu, Moreland, & Phu, 2011;Palomares, Pettet, Vildavski, Hou, & Norcia, 2010;, and many more.…”
Section: Introductionmentioning
confidence: 99%